If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3x + -7 = 0 Reorder the terms: -7 + 2x + -3x = 0 Combine like terms: 2x + -3x = -1x -7 + -1x = 0 Solving -7 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -1x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -1x = 0 + 7 -1x = 0 + 7 Combine like terms: 0 + 7 = 7 -1x = 7 Divide each side by '-1'. x = -7 Simplifying x = -7
| 6(7a+7)=420 | | 6(-3+2k)=-66 | | 2(7a+2)=18 | | 2(-4n+7)=6 | | 2(-6+3w)=-36 | | 7(2n-6)=112 | | 2(10+b)=30 | | 5(-9-d)=-90 | | 3(-1b+2)=33 | | 4(-1k+4)=20 | | 6(1t+3)=30 | | 6(3+4b)=18 | | 5(2t-6)=90 | | 5(1t+6)=-10 | | 5(5+4w)=-35 | | 6(-9-6m)=-378 | | 4(8-6d)=224 | | 2(-8-4w)=-64 | | 7(6k+8)=350 | | 5(3m+7)=35 | | x^2-x+42= | | 5(2n+6)=0 | | 2(-6t-8)=-112 | | 5(-9+x)=-90 | | 3(7b+8)=150 | | 7(5w-8)=-371 | | 4(-5-m)=-24 | | 3(-4w+2)=-78 | | 7(-2b-2)=-112 | | 3(4t+7)=-63 | | 3(-5d+1)=-147 | | 2(5w+9)=68 |